2017
DOI: 10.1371/journal.pone.0173480
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tooth whitening strips on fatigue resistance and flexural strength of bovine dentin in vitro

Abstract: ObjectiveTo determine the effects of whitening strips on bovine dentin fatigue resistance and flexural strength in vitro.Materials and methodsA total of eighty bovine dentin specimens (2x2x17mm) were treated with either: control glycerine gel on plastic film wrap or whitening strips containing 9.5% hydrogen peroxide. Treatment was applied for 30 minutes, twice a day, for 1- or 4-weeks. After the last treatment, ten specimens per group were randomly selected to undergo fatigue testing (106 cycles, 3Hz, 20N) whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Additionally, it has been suggested that bleaching procedures may cause protein denaturation with free radicals that break the double bonds, leading to the degradation of the resin–dentin bond (Plotino et al, ). However, Tam, Kim, and De Souza () stated that the HP did not induce significant changes in the inorganic and organic contents of the tooth, but they observed the oxidation of the organic structure by the release of reactive oxygen species. No publication has established a correlation between a drop in the bond strength and structural changes along the bleached dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been suggested that bleaching procedures may cause protein denaturation with free radicals that break the double bonds, leading to the degradation of the resin–dentin bond (Plotino et al, ). However, Tam, Kim, and De Souza () stated that the HP did not induce significant changes in the inorganic and organic contents of the tooth, but they observed the oxidation of the organic structure by the release of reactive oxygen species. No publication has established a correlation between a drop in the bond strength and structural changes along the bleached dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HP may not only oxidize the benzene ring in AAAs but also saturate double bonds in other AAs, which can also change the protein structure. Teeth treated with HP demonstrate decreased mechanical behavior, including fracture toughness (Tam and Noroozi 2007), fatigue resistance, flexural strength (Tam et al 2017), elastic modulus, and creep (Elfallah et al 2015). The assumption that the declined mechanical performances result from the oxidation of organic matrix by HP is well accepted (Jiang et al 2007; Eimar et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have used bovine teeth as substitutes for human teeth because of the difficulty in collecting intact extracted human teeth for laboratory studies [ 48 , 49 ]. However, bovine coronal dentin has larger dentinal tubules than in human dentin.…”
Section: Factors That Affect Bond Strength Measurementmentioning
confidence: 99%